Zur Etablierung der deutsch-niederländischen Staatsgrenze als Dialektgrenze im Nordniedersächsischen: Sprachliches Wissen, Wahrnehmung linguistischer Laien oder beides? - Hohenstein, Line-Marie (Linguistik Online, 2017)
Dialects in general are losing more and more their genuine structures, meaning the structure of the dialect has increasingly overtaken some standard variety structures. Such changes, however, were as well observed in border dialects, for example Low-German and Dutch ones (see Kremer 1979 and Giesbers 2008 and Smits 2011). The German and Dutch standard variety to those the dialects have adverged are that different in their structure that the dialects now diverge among themselves at some regions across the border. This process led to the fact, that the state border between the Netherlands and Germany has become an isogloss. Besides these facts it could have been proven by Kremer (1984) and Giesbers (2008) with modern methods like mental maps that also the perception of the state border has changed – it has become an isogloss on their mental map as well. This article circles the question, if those linguistic divides (i. e. „sprachliche Bruchstellen“, cf. Kremer 1993: 26) can also be found in other areas across the German-Dutch border such as in the area, where North lower Saxon is spoken. To investigate the potential change of each dialect in favor of the particular standard variety, I chose linguistic phenomena of the genuine homogeneous North lower Saxon dialect and surveyed them with traditional methods (i.e. translating sentences). Besides that, I applied the method mental maps and asked in two villages, which are located in Germany and in the Netherlands, where to speak (mainly) the same. In a last step I correlated those results, to see if both – perception and status quo of the dialect structure – match.